Transformation Of Local Wisdom Values In Management Of Village Funds (Study In Villages In Kupang Tengah District) - Yohanes Demu; Siprianus G. Tefa (CV. AFDIFAL MAJU BERKAH, 2023)
Normative management of village funds in Permendagri Number 20 of 2018 hints at community participation at every stage so that the community becomes the planner as well as implementer and financial supervisor in the village. The Development Village Index (IDM) value is an indicator of successful development and increased welfare of village communities. The purpose of this study was to see the local wisdom implemented in Baumata Timur Village and Mata Air Village in managing Village Funds. This research is a qualitative descriptive research with a case study approach. Sources of data in this study are primary data obtained through observation and interviews as well as secondary data obtained through documentation. The data analysis technique used is data reduction, data presentation and conclusion. The results of this study indicate that the value of local wisdom in East Baumata Village in managing village funds can be seen when planning the use of village funds through the